Hubungan Tingkat Kreativitas dengan Prestasi Belajar pada Siswa Sekolah Dasar Kelas III SDN Karang Tengah 7 - Selvina Salsabila; Siti Annisa Ramdhini (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2020)
This study discusses the relationship of creativity with the learning outcomes of class III students at SDN Karang Tengah 7. This study aims to determine the creativity of class III students at SDN Karang Tengah 7. To find out the learning outcomes of class III students at SDN Karang Tengah 7. To find out the relationship between creativity with the learning outcomes of third grade students at SDN Karang Tengah 7. This study uses a quantitative approach. This type of research is a correlational study using a bivariate correlational research design. The results of the study stated that students' learning creativity in general was in the medium category with a percentage of 69.24%. The results of the data analysis show that there is a significant relationship between the creativity of students in grade III SDN Karang Tengah 7 in the academic year 2019-2020.